Analysis of combined radiation and convection heat transfer inside a porous medium with heat source electronic devices. (April 2022) - Nahal, Ali Mokhtari; Nobakhti, Mohammad Hassan; Aghanajafi, Cyrus; Khayat, Morteza
In this study, a numerical study is performed on the cooling phenomenon of three heat source electronic devices. The electronic devices are cooled in the form of natural heat transfer by the airflow in a porous medium. Electronic devices are installed on the boundary walls of a square environment. Cooling simulations are performed by drawing flow lines and constant temperature lines. Our main goal is to find the highest cooling rate in different Darcy numbers and different Rayleigh numbers in our investigation. The range of Darcy numbers and Rayleigh numbers is between 0.0001 to 0.01 and 1000 to 100, 000, respectively. Our investigation showed the maximum cooling is obtained at the Darcy number of about 0.01. And also, by decreasing the value of Darcy number, a higher cooling rate for the hot boundary walls is achieved.